"Try Some Polish"as examples of innovative teaching materials for teaching Polish as a foreign language - a case study - Banach, Agnieszka; Dębska, Małgorzata (Activation-innovation-inspiration in (glotto) didactics, 2022)
On the social networking site Instagram there is increasing amount of the profile connected with education, including profiles concerning foreign language teaching. Responding to the pandemic situation and the related restrictions, members of Student Research Group of Glottodidactics at the University of Lodz affiliated with the Department of Applied and Cultural Linguistics decided to create an educational account on Instagram “Try some Polish” and publish content related to the Polish language and culture. The profile consists of three main sections: lexical, where new vocabulary asscociated to specific topic apears entertaining, which is based on publihsing language games and plays activating the recipients; and cultural, which contains interesting information on Polish culture in its broad sense. After the analysis the statistics of the published posts and after conducting the survey among the account’s followers, it may be concluded that the virtual didactic activity of the students and PhD candidates is positvely perceived by learners of Polish language, and Instagram might be a suitable platform to support of didactic process.